2009
DOI: 10.1093/annonc/mdn589
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens, oral contraceptives and hormonal replacement therapy increase the incidence of cutaneous melanoma: a population-based case–control study

Abstract: Our study suggests a cumulative dose-dependent increased risk of CM with the use of estrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 24 publications
4
74
1
4
Order By: Relevance
“…Feskanich et al [12], using data from the Nurses' Health Study, and Koomen et al [13], using linked data from Holland, found an increased melanoma risk with oral contraceptive use. In contrast, early results from our own research group [14], two meta-analyses [10,15] and a pooled analysis of case-control studies [16] found no evidence for an association between the two.…”
Section: Introductionmentioning
confidence: 99%
“…Feskanich et al [12], using data from the Nurses' Health Study, and Koomen et al [13], using linked data from Holland, found an increased melanoma risk with oral contraceptive use. In contrast, early results from our own research group [14], two meta-analyses [10,15] and a pooled analysis of case-control studies [16] found no evidence for an association between the two.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a large population-based case-control study, we showed a cumulative dosedependent association between the use of estrogens, for both OC and HRT, and the incidence of CM [5]. The clinical relevance of our findings, however, requires further study.…”
Section: Introductionmentioning
confidence: 60%
“…It is possible that there are more White men than women in South Africa who have outdoor occupations, who might wear fewer clothes than women, and who use less personal photoprotection than women. Whether any gender difference in incidence or body site distribution goes beyond societal differences is uncertain at present (40,41).…”
Section: Sexmentioning
confidence: 99%